Accounting ethics education : teaching virtues and values - Pinheiro, Margarida M.; Costa, Alberto J. (London ; New York : Routledge, 2021)
"Accounting education ought to prepare future professionals to enter a principle-based, rules-oriented field of activity wherein technical knowledge of accounting standards (principles, rules and decision-procedures) and ethical awareness (capacity to discern moral issues and resolve ethical dilemmas) are crucial. Such endeavor is best performed by the accountant's adherence to the principles of the accounting profession, by individuals and firms who follow the appropriate rules, act according to the codes of conduct adopted by their profession, and exercise clear judgment whenever they address financial transactions, and consider/assess the state of a given business. Accounting Ethics Education: Making Ethics Real gathers a diversity of contributions from invited well-known experts and other specialists. It promotes comprehensive reflection around key trends, discussing and highlighting the most updated research on accounting ethics education, being an essential and useful reference in the field. In the performance of accounting tasks, the accountant should be educated and supported in the skills development and habit formation to solve accounting problems and recognize moral issues and resolve ethical dilemmas that will be encountered in their special tasks. Also, the book provides a moral map for identifying and acting on values when difficult situations arise. Examining multiple perspectives, the book improves the scholarly debate by providing cutting edge and insightful research, vital for all those interested and immersed in these matters. It will be of great value to academics, students, researchers, and professionals in the fields of accounting, accounting education and ethics"--
Includes bibliographical references and index.
Description based on print version record.
Keywords: Accounting -- Study and teaching; Accounting -- Moral and ethical aspects